Analisis Profitabilitas Dalam Pemberian Kredit Pada Koperasi Kredit Unam Berastagi - Novrianta S. Brahamana; Miftahuddin Miftahuddin; Ahmad Prayudi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This study aims to find out and prove "Analysis of Profitability in Giving Credit to the Berastagi Unam Credit Cooperative" This type of research is a type of quantitative descriptive research, namely explaining the relationship between variables by analyzing numerical data (numbers) using statistical methods through hypothesis testing. intended to find out "The Level of Profitability in Giving Credit to the Berastagi Unam Credit Union" ".